Performance Analysis Of Simpang Empat Matang Seulimeng Roundabout, West Langsa District, Langsa City - Azkia Salsabila; Lis Ayu Widari; Teuku Mudi Hafli; Said Jalalul Akbar; Muthmainnah (Universitas Iskandar Muda, 2025)
In West Langsa District, Langsa City, you can find Gampong Matang Seulimeng. Langsa is now home to a sizable urban population. Obviously, this will lead to daily traffic congestion in Langsa City, which in turn will result in delays, long queues, and congestion at intersections and highways. Many cars, each with its own agenda, starting point and end destination, collide at the roundabout. There are many roads leading to the Simpang Matang Seulimeng Roundabout in Langsa City, including Jalan Prof. A Madjid Ibrahim and Jalan Jendral Sudirman. The research team in Matang Seulimeng wanted to know how well the roundabout at the intersection worked and what kind of side obstacles it encountered. The results of this study, which uses PKJI 2014, suggest a new approach to improve the functionality of roundabouts. The medium class score of 494 was obtained from the data of side obstacles. The saturation degree value is 0.37 (LOS B) on Jl Prof. A. Majid AB. The intersection, 0.53 (LOS B) on Jl. Jenderal Sudirman BC, 0.87 (LOS D) on Jl. Prof. A. Majid CD, and 0.53 (LOS B) on Jl. Jenderal Sudirman DA were determined through roundabout performance analysis. These values indicate stable traffic, unstable traffic, unstable traffic, and stable traffic, respectively.